INTEROPERABILITY AND EFFECTIVENESS OF INDUSTRIES IN THE SUB-SAHARAN AFRICA (SSA) EVIDENCE FROM NESTLE NIGERIA PLC. - Kensington Onajero OHWO (Management & Marketing)
The study was conducted to ascertain the effectiveness of interoperability in manufacturing companies in sub-Saharan Africa. The study used the ex-post facto research design and secondary data on the variables (interoperability, profitability, and liquidity) for 2013 -2018 were obtained from the audited annual report of Nestle Nigeria PLC for the relevant years. Linear regression was used to test the hypothesis at a 5% level of significance and ANOVA was also used to test the significance of the model. The study finds that there is a significant effect of investment in ICT (interoperability) on the bottom-line of Nestle Nigeria thereby having a positive impact on the company’s profit, while at the same time, investment in ICT does not have any significant effect on the level of liquidity in Nestle Nigeria. The study therefore concludes and recommended that manufacturing companies should ensure they deliberately set funds aside for continuous investment to improve the level of investment in ICT in their operations.